Is it Good to be Born as a Late Preterm Infant? - Marjana Jerković Raguž; Katarina Šoljić; Željka Prce; Vinka Mikulić; Tatjana Barišić; Svjetlana Grgić (Clinical and Experimental Obstetrics & Gynecology, 2022)
Background: This study conducted at the Clinic for Children’s Diseases of the University Clinical Hospital Mostar, aims to highlight the characteristics, frequency, course, most common complications and treatment outcomes of pregnant women and their late preterm infants according to gestational age. Methods: This study is a retrospective epidemiologic study for the period from 1/1/2018 to 31/12/2021. The study included all the preterm infants who were born at a gestational age from 34+0/7 to 36+6/7 weeks and their mothers. Results: In the period under study, a total of 7178 infants were born, of which 253 (3.52%) were late preterm infants. The results show that most mothers were between 30 and 39 years of age, pregnant for the first time with a single pregnancy, delivered by caesarean section, with complications in 53.1% of the pregnancies. All the analyzed pathological conditions were more common in the pregnancies which ended at 34 weeks. Our results indicate that the late preterm babies had a good birth weight (53.8%) and high vitality scores (93%) at birth, but these scores were not confirmed on the first day of life. A significant number of late preterm infants had some pathological condition which was treated in the intensive care units (ICU) (p < 0.001). Conclusions: The study concludes that half of the pregnant women had risk factors which were the basis for the preterm births and the development of complications in the late preterm infants. Furthermore, despite good birth weight and vitality scores at birth, only one fifth of the late preterm infants were not treated with medications or developed pathological conditions, whereas only one third required no intensive care treatment. It is, therefore, necessary to improve the monitoring and understanding of such pregnancies, implement antenatal corticosteroid therapy, and increase parental awareness to ensure long-term and frequent monitoring of late preterm infants by pediatricians.